2021
DOI: 10.1177/03611981211003572
|View full text |Cite
|
Sign up to set email alerts
|

Performance Evaluation of Different Insulating Materials using Field Temperature and Moisture Data

Abstract: Including insulation layers in pavement structures has become a common strategy to minimize frost penetration in cold regions. This study investigated the performance of two different insulation materials, extruded polystyrene board and bottom ash, in a test road in Edmonton, Alberta, Canada, eight years after construction. The two insulation materials were used in a fully instrumented test road, including three insulated sections 20 m in length. The insulated sections are as follows: the first section has 1 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 15 publications
0
16
0
Order By: Relevance
“…There is a high correlation between the D 0 value and the temperature of the HMA layer ( 14 , 21 ). Polystyrene board leads to a higher HMA layer temperature in summer and lower HMA layer temperature in winter ( 5 ), and thus increases the likelihood of pavement damage ( 5 , 15 ). This fits with the higher deflection values observed for the pavements insulated with polystyrene board after five years of operation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…There is a high correlation between the D 0 value and the temperature of the HMA layer ( 14 , 21 ). Polystyrene board leads to a higher HMA layer temperature in summer and lower HMA layer temperature in winter ( 5 ), and thus increases the likelihood of pavement damage ( 5 , 15 ). This fits with the higher deflection values observed for the pavements insulated with polystyrene board after five years of operation.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that the physical properties of BA make it a high-quality base material (11,12). BA acts as an insulation layer to protect the subgrade from frost in winter (5,8,13). Haghi et al (8,(14)(15)(16) found that polystyrene and BA protected the subgrade layer from frost.…”
mentioning
confidence: 99%
See 3 more Smart Citations